Pengaruh Akuntabilitas, Transparansi dan Sistem Akuntansi Keuangan Desa dalam Pengelolaan Keuangan Desa - Anggi Alfiani; Sri Dwi Estiningrum (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This research on accountability, transparency and village financial accounting system is intended to determine the effect on village financial management. The use of the associative method was chosen as a reference to determine and test whether there is an influence between variables. This study takes a non-probability sample where the sample determined by the researcher is 70 respondents consisting of Pule villagers who have the criteria determined by the researcher. Primary data and secondary data are used by researchers to test between several variables, where related data is collected through questionnaire techniques. The results of the multiple linear regression analysis show that there is an influence of accountability, transparency and village financial accounting systems in managing village finances in Pule village, Pule sub-district, Trenggalek district.